Viability of fibroblast cells on the clove (Syzygium aromaticum) leaves ethanol extract - Felicia, Anindhita Cindy; Sugiaman, Vinna Kurniawati; Pranata, Natallia (Padjadjaran Journal of Dentistry, 2019)
Introduction: Various active compounds of herbal plants that are known to accelerate the wound healing process are flavonoids, tannins, and saponins. One amongst them is clove (Syzygium aromaticum), with the leaves as the most common part to be used as herbal medicine due to the antibacterial, anti-inflammatory, and antioxidant properties. However, the use of the biocompatibility of clove leaves as herbal medicine is still unknown. Therefore, this study was aimed to determine the cytotoxicity effects of clove leaves ethanol extract on the fibroblast cells and safe dosage (IC50) for medicinal use. Methods: Phytochemical tests using the Farnsworth method and viability test was performed using the laboratory experimental with post-test only control group design. The samples were divided into seven concentrations; 500, 250, 125, 62.5, 31.25, 15.63, and 7.81 μg/ml, with three repetitions (triplo) towards the fibroblast cells. Viability test was performed using MTS assay. Results: Based on the results obtained from one-way ANOVA statistical test, there was a significant difference between the percentage of cell viability and each concentration (α ≤ 0.05), with IC50 value of 344.814 μg/ml. Conclusion: Clove (Syzygium aromaticum) leaves ethanol extract showed a high percentage of cell viability at the concentrations below the IC50 value.Keywords: Clove leaves, cytotoxicity, fibroblast cell, MTS assay, periodontal diseases, viability.